Prvi koraki v judo vrtcu - Stavrev, Vesna (Šport (Ljubljana), 2014)
Judo kindergarten is an organised sport activity which is becoming increasingly popular among children in Slovenia. The judo kindergarten programme includes different basic motor activities and basic judo elements. When performing judo exercises children develop their motor abilities, learn some judo basics and get familiar with the ethical principles and rules of judo. The major goals of the programme include teaching of children to work in pairs and in a group, to help each other, to respect each other despite their mutual differences as well as to follow the rules and fair play. The judo kindergarten programme positively affects the childćs overall development. The abilities and the knowledge that a child acquires in the judo kindergarten can also be applied in everyday life.
Keywords: borilne veščine; borilni športi; combat sports; ethical principles; etična načela; guidance for the instructor; judo; judo basics; martial arts; napotki za vaditelja; osnove juda; predšolski otroci; preschool children; sport; šport; športna dejavnost; vrtec